Finding the Hidden Driveways: Observing Students at Work - Simon Hole (Networks: An Online Journal for Teacher Research, 1998)
My brother and I spent part of my 17th summer counting dogs for the township we lived in. At 15 cents per pooch, taking dog census was hardly going to make us rich, but it kept us busy and we could set our own schedule, which is why it was mid-August before we started driving down the last country road of the township.